Intellectual Property and Its Protection through Cyber Laws: Indian Perspective: Challenges and Solutions for Intellectual Property Protection in the Digital Age (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Property can be broadly classified into tangible property and intangible property. Tangible property can be in the form of land, where house, building, factory, furniture etc. Intangible property is something which is not visible but is recognised by law as a property. One such type of property which is recognised by law is called intellectual property. This property arises from the creation of the mind of a person and its value can be in millions of rupees. A category of law which protects the rights of the possessor of intangible products of ingenuity or innovation is called intellectual property. Special rights are provided to definite owners of artistic work, literary work, symbols, designs and technical inventions. A collective name given to these rights is called Intellectual property rights and the property protected under these rights is called intellectual property.Intellectual properties such as copyright, trademark, design and circuit design are interwoven with electronic technology and therefore more affirmative protective laws are required to protect inventions. In today’s globalised world it is essential to save the real owners of intellectual property from theft and economic losses. The real owners must not only have knowledge of their intellectual property rights and cyber laws but also be aware of conflict of law and international law. Though the laws have been incorporated by the Government, it is the duty of the owners of intellectual property rights to invalidate and reduce mala fide acts of criminals by taking proactive measures. This paper explicates various issues associated with the protection of intellectual property through cyber laws in India.